Ultra-porous cellulose nanofibril aerogel films as excellent triboelectric positive materials via direct freeze-drying of dispersion. (1st December 2022) - Song, Yiheng; Bao, Jiangkai; Hu, Yang; Xu, Menghan; Yang, Zhibo; Liu, Yating; Yang, Quanling; Xiong, Chuanxi; Shi, Zhuqun
Abstract: Cellulose-based materials hold great promise for excellent triboelectric materials due to their fascinating attributes. However, few works have studied in a detail and systematic manner of the relationship between the cellulose structure and the output performance. Herein, we report the preparation of TEMPO-oxidized cellulose nanofibrils (TOCN) aerogel films with a high specific surface area of 134.1 m 2 /g as a high-performance inorganic filler-free triboelectric positive layer by a simple and controllable method. TOCN aerogel films with different structures were prepared in one-step by a direct freeze-drying process from quick freezing TOCN dispersions. The effects of four gradually increasing freezing rate methods on TOCN aerogels were proposed and studied. And the addition of TBA improved the freezing rate, reduced the volume expansion and decreased the surface tension, which were beneficial to the triboelectric properties of TOCN aerogel films. Effects of the nanofibril structures and device parameters on their triboelectric output performance were also discussed in detail. Without the addition of any fillers and chemical modification, the pure TOCN aerogel film based triboelectric nanogenerator (TENG) devices achieved a record power density of 156 mW/m 2 . Meanwhile, external influencing factors of the device and recyclability of the pure cellulose triboelectric material were systematically investigated. This work would provide a comprehensive guidance for the design and preparation of high-performance cellulose-based triboelectric positive materials. Graphical Abstract: TEMPO-oxidized cellulose nanofibril aerogel films for triboelectric positive layer ga1 Highlights: TBA can increase the freezing rate and reduce volume expansion of TOCN dispersions. Freezing rate was found to significantly affect specific surface area of aerogel. The TOCN aerogel film exhibited high SSA of 134.1 m 2 /g by a simple method. A high power density of 156 mW/m 2 was achieved for the TOCN TENG. Pure TOCN-based triboelectric materials show advantageous reprocessability.